Unions, wage gaps, and wage dispersion: New evidence from the Americas - Fernando Rios-Avila; Barry T. Hirsch (Institute for the Study of Labor (IZA), 2012)
Using a common methodology, the effects of unions on wage levels and wage dispersion are estimated for two neighboring countries, Bolivia and Chile, and for the U.S. The analysis shows that unions have broadly similar effects on the wage distribution within these three economies. The findings suggest that the political economy of unions, coupled with market constraints on labor costs, produce commonality in union wage effects that transcend other economic and institutional differences.
Keywords: J31; J51; 330; unions; wages; wage dispersion; Latin America; Lohnbildung; Lohnstruktur; Gewerkschaft; Bolivien; Chile; USA